RELATIVE FISHING POWER OP TRAWLERS OPERATED OFF COCHIN - Chakraborty, D; Banerji, S K (Indian Journal of Fisheries, 2011)
ALL vessels do not have same fishing power. The absolute fishing powerof a vessel is measured in terms of the fishing mortality generated by it. Butsince the latter cannot be measured directly, a relative fishing power of avessel has been defined as the ratio of the catch per unit fishing time of thevessel to that of another fishing vessel taken as standard when both arefishing on the same ground and the same density of fish. In this way, afishing power can be allotted to each vessel. Once the relative fishing powerof different vessels are known, it will be easy to Compute the totalintensity of fishing effort, an accurate estimate of which is so essential inthe study of stock assessments of fisheries